Scenes of Daily Life in the Mosaics of Ostia - Licordari, Antonio; Pellegrino, Angelo (Actual Problems of Theory and History of Art, 2021)
During the heyday of mosaic in Ostia, that is to say during the imperial age, the patrons were families of a more or less wealthy bourgeoisie. They were content to embellish the black and white mosaic floors with a figurative repertoire often of low artistic quality and with simple and not particularly original motifs. The more affluent classes, however, were influenced by Hellenistic figurative culture and made frequent use of colour.Mythological and fantasy themes with an abundance of animals, gods, and sea monsters are especially common in large areas. These motifs derive from repertoires that had been widespread since the late Hellenistic period and were repeated with minor variations. Local artists could be more or less skilled in understanding and reworking the subjects. But Ostia, a lively and animated city due to its port and its trade with the major Mediterranean cities, also offers a vast repertoire of scenes dedicated to daily life, on which we intend to focus our attention.A number of main themes can be identified, such as sport (boxers, wrestlers, and especially aspects of circus competitions), rural life (depictions of the seasons, agricultural activity), the world of commerce with the scenes on the Corporation Square, depictions of socially humble people, the measurement of grain and the provisioning of the urban population, and “Nilotic” hunting and fishing scenes.
Keywords: Ancient Ostia; mosaics; daily life; baths; trade; sport